Neurological pathogenesis of SARS-CoV-2 (COVID-19): from virological features to clinical symptoms - Yoshitaka Kase; Hideyuki Okano (BMC, 2021)
Abstract Since the worldwide outbreak of coronavirus disease 2019 (COVID-19) in 2020, various research reports and case reports have been published. It has been found that COVID-19 causes not only respiratory disorders but also thrombosis and gastrointestinal disorders, central nervous system (CNS) disorders, and peripheral neuropathy. Compared to other disorders, there are low number of research reports and low number of summaries on COVID-19-related neural disorders. Therefore, focusing on neural disorders, we outline both basic research and clinical manifestations of COVID-19-related neural disorders.